Colonizing Black Female Bodies Within Patriarchal Capitalism: Feminist and Human Rights Perspectives. (9th December 2016) - Benard, Akeia A. F.
This article argues that the dynamics underlying the fundamental gendered/raced/sexual relationships that were created under colonialism exist in the same form in global patriarchal capitalism and pop culture, including mainstream music and pornography. It also explores contemporary Black feminist literature that critiques foundational Black feminist thought which views individual examples of "empowered" (wealthy, marketed/marketable) women of color as evidence of Black female liberation. Finally, in an effort to bridge foundational Black feminist thought with contemporary critiques, I discuss media representations of the Black female body in the context of human rights and sexual rights, as this offers global and historical perspective without minimizing the agency of those whose bodies have historically been exploited for profit.Public Health Statement: This study argues that hypersexualized and degrading images of women of color in media contradict the World Health Organization's current definition of sexual health and sexual rights. Viewing the history and use of this imagery provides a theoretic framework for understanding the negative mental, physical, and sexual health consequences of degrading imagery and can aid in realizing positive sexual health outcomes for women of color.